Design and Implementation of a Minimalist Programming Language Stab using Flex, Bison and LLVM - Gautam, Abhilekh; Lamichhane, Bishal; Lamichhane, Ankit; Bhattarai, Aashan; Shrivastava, Amit (Journal of Science and Technology, 2024)
We present the development of a minimalist programming language using Flex, Bison, and LLVM (Low Level Virtual Machine). The language supports essential programming constructs, including data types, loops, conditional statements, arrays, and functions. The project involved building a compiler capable of translating high-level language constructs into machine code. Challenges such as error handling and symbol table management were addressed effectively, ensuring the compiler’s reliability and functionality. This project demonstrates the successful integration of Flex, Bison, and LLVM in a compiler framework, serving as a valuable educational tool. It has significant implications for Nepalese education, where practical opportunities in compiler construction are limited. By offering a concrete example of language design and implementation, this work aims to enhance the computer science curriculum in Nepalese universities, bridging the gap between theoretical concepts and practical application.